2000
DOI: 10.1002/1096-9896(2000)9999:9999<::aid-path692>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Role of macrophage scavenger receptor in endotoxin shock

Abstract: Lipopolysaccharide (LPS) is known to bind to several receptors on macrophages, including CD14 and macrophage scavenger receptor class A types I and II (MSR-A), and stimulates macrophages to release various inflammatory mediators. MSR-A recognizes a broad range of polyanionic ligands such as chemically modified lipoproteins, LPS of Gram-negative bacteria, and lipoteichoic acid of Gram-positive bacteria, suggesting a role in host defence. In this study, mice lacking MSR-A were used to elucidate the role of MSR-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…SR-A in LPS responses have yielded different outcomes, probably due to different challenging protocols [36,37]. The SR-A À/À mice were not included in our study, but the phenotypes were always more severe in the DKO mice than in those lacking MARCO only, indicating a functional role for both receptors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…SR-A in LPS responses have yielded different outcomes, probably due to different challenging protocols [36,37]. The SR-A À/À mice were not included in our study, but the phenotypes were always more severe in the DKO mice than in those lacking MARCO only, indicating a functional role for both receptors.…”
Section: Discussionmentioning
confidence: 98%
“…Further, the conclusion that class A SR contribute to the microbial clearance upon infection is also supported by the findings in a study in which WT and SR-A À/À mice were challenged with Staphylococcus aureus [35]. However, the studies addressing the role of SR-A in LPS responses have yielded different outcomes, probably due to different challenging protocols [36,37]. The SR-A À/À mice were not included in our study, but the phenotypes were always more severe in the DKO mice than in those lacking MARCO only, indicating a functional role for both receptors.…”
mentioning
confidence: 79%
“…For example, macrophage death induced by combinatorial PRR signaling may be a host defense mechanism against those pathogenic organisms that seek safe haven inside living macrophages (36)(37)(38). With regard to evidence that SRA and TLR4 may functionally interact in vivo, three independent reports have shown that mice lacking SRA have altered cytokine and survival responses to LPS (39)(40)(41), although the mechanisms of the altered responses were not elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IRF3 also can function as a coactivator of NF-B-regulated genes (50), and so inhibition of IRF3 by SRA might prevent activation of genes involved in the inflammatory response. This hypothesis may provide insight into how SRA affects the inflammatory response to LPS in vivo (39)(40)(41). Addressing these questions and probing combinatorial PRR apoptosis signaling in vivo may yield new therapeutic strategies related to diseases and host defense processes in which the balance between macrophage survival and death plays important roles.…”
Section: Discussionmentioning
confidence: 99%
“…20 Our current finding that SR-A Ϫ/Ϫ , MARCO Ϫ/Ϫ , and DKO mice showed defective bacterial clearance but produced higher levels of inflammatory cytokines after intraperitoneal NM challenge is consistent with most previous reports 11,36 ; although enhancement of LPS responses has also been reported. 37 Apart from the secretion of bioactive mediators, another hallmark of inflammation is the infiltration of specific leukocyte populations into affected tissue. This process is regulated by a series of complex changes in damaged tissue, vascular endothelia, and migrating leukocytes.…”
mentioning
confidence: 99%